Efficient Inverted Polymer Solar Cells with ITO Cathode Modified by Zinc Oxide and Polyethylene Oxide Bilayers. Issue 18 (21st June 2018) - Huang, Youhuan; Cai, Ping; Ren, Peng; Zhang, Xiuyun; Du, Yusong; Zou, Zhuoliang; Xiong, Jian; Xue, Xiaogang; Zhang, Jian; Chen, Junwu
Abstract : For inverted polymer solar cells (PSCs), zinc oxide (ZnO) with various advantages are typically used as cathode buffer layer, but the existing surface traps/detects of ZnO layer obviously restrict device performance. In this work, the authors introduce polyethylene oxide (PEO) with high molecular weight of 300 thousands to modify the surface of ZnO layer on ITO cathode for inverted PSCs, where PEO possesses the particular advantages of easy accessibility and low cost. Compared with the ITO modified by pure ZnO and PEO layer, the ITO modified by ZnO/PEO bilayers shows the similarly good transparency, the lowest work function, the best surface morphology, and contact property. ZnO/PEO bilayers can provide the optimal energy alignment and interface contact between ITO and active layer, and efficiently eliminate the surface defects of ZnO layer. Therefore, the ITO/ZnO/PEO‐based device exhibits the best photovoltaic performance with the PCE of 9.57% compared to the ITO/ZnO‐based device (8.42%) and the ITO/PEO‐based device (8.16%). The impressive results suggest that ZnO/PEO bilayers should be promising cathode buffer layer for high‐performance inverted PSCs. Abstract : ZnO/PEO bilayers are introduced to modify the ITO cathode for inverted PSCs. Compared with pure ZnO and PEO layer, ZnO/PEO bilayers can offer the optimal energy alignment and interface contact between ITO and active layer, and efficiently eliminate the surface defects of ZnO layer. The ITO/ZnO/PEO‐based device exhibits the highest PCE of 9.57% compared to the ITO/ZnO‐based device (8.42%) and the ITO/PEO‐based device (8.16%).